Orchids diversity and conservation assessment in coastal heath forest of Terengganu - Md Isa, Siti Fatimah (2015)
Coastal heath forest in Terengganu is a type of forest that is not well known to the publics. The forest is locally known as "Hutan Paya Gelam" because plants that reside in the forest are mostly abundance with stunted Melaleuca cajuputi. Generally, the plant diversity in the heath forest is believed to be lower than other lowland forest due to the lacking of nutrient, exposure to a very hot weather, prone to natural forest fire and acidic sandy soil. Furthermore, the orchid diversity was poorly studied in heath forest and the information especially on the coastal heath forest of Terengganu was very limited. Hence, a diversity and conservation assessment study was conducted from 2013 to 2014 focusing on the Orchidaceae family in the coastal heath forest of Dungun (in Jambu Bongkok Forest Reserve, JBFR) and Setiu, Terengganu. The objectives for this study were to document orchids species in the forest, to investigate orchids habits and morphological characters, to study the diversity and to assess conservation status of orchids in the area. A total of 26 taxa in 14 genera from 2 subfamilies, namely Orchidoideae and Epidendroideae were collected and recorded via random sampling within the area. The species identification was done by referring to the identification book of orchids, herbarium specimen and also advises from the experts. From the identified species, all collected species were classified as "Least Concern" in accordance to the IUCN Red List Categories and Criteria version 2014.3. The diversity of orchids in the area was shown to be high using Shannon Diversity Index, H with JBFR, H = 3.20 and Setiu, H = 2.81. While for Simpson Diversity Index, D the value for JBFR, D = 0.89 and Setiu, D= 0.90. Several survival factors adopted by the orchids species to maintain their existence in the harsh environmental condition of the heath forest were also identified. One of the morphological characters is having a "pseudobulb" structure to store water and nutrient especially during the extreme dry season. The study also shows that 81% of the identified species were epiphytic species. Being an epiphytic species, which anchor on the tree trunk, is another adaptation of the orchids to survive given that the acidic sandy soil is not favorable for the growth of the species. The obtained results can be used as the baseline information on plant diversity in coastal heath forest and also can be used as the preliminary data for further assessment on orchids species in Terengganu.